Preparation method of high-entropy alloy film with adjustable components and crystal phase

Through magnetron sputtering technology, the vacuum degree and sputtering parameters are controlled to prepare high-entropy alloy films, which solves the problem that the crystal phase structure and composition of high-entropy alloy thin films in the prior art is difficult to control, and a low cost and high effect preparation method is realized.

CN119843229AActive Publication Date: 2025-04-18XIAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411467204.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-04-18
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The crystal phase structure and composition of existing high-entropy alloy films are not easy to control, and expensive instruments and equipment are required, which has high production costs.

Method used

Magnetically controlled sputtering technology is used to prepare high-entropy alloy films by installing atomic alloy targets such as FeCoNi ternary, metal targets such as Mo, Cu, etc. to control the vacuum degree and sputtering parameters.

Benefits of technology

The crystal phase structure and composition of high-entropy alloy film are adjusted, which simplifies the preparation process and greatly reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843229A_ABST
    Figure CN119843229A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-entropy alloy film with adjustable and controllable components and crystal phases. The preparation method comprises the following steps: step 1, cutting a Si wafer into square pieces; 2, a magnetron sputtering system is started, a FeCoNi ternary equal-atomic-ratio alloy target material is installed at a first target position, a Mo metal target material is installed at a second target position, a Cu metal target material is installed at a third target position, then a cooling water system is started, then the square sheet is placed at the dead center of a sample disc and placed in a vacuum chamber cavity, and finally vacuumizing is conducted; step 3, opening a vacuum indicator, controlling the rotating speed of the sample table to be 5r / min, introducing pure Ar gas as sputtering gas, and keeping the vacuum degree by controlling the flow of the Ar gas; and 4, the sputtering power and the sputtering time are set, the target baffle is opened, sputtering is started, and the high-entropy alloy film is obtained. The invention discloses a preparation method of a high-entropy alloy film with adjustable and controllable components and a crystal phase. The problem that the crystal phase structure and the components of an existing high-entropy alloy film are not easy to control is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-performance alloy materials, and in particular relates to a method for preparing a high-entropy alloy film with adjustable components and crystal phases. Background Art

[0002] With the continuous progress of society and the rapid development of science and technology, the demand for high-performance alloy materials in my country and even the world's economic development is growing. Traditional alloys, that is, single-principal alloy materials, can no longer meet the requirements of various industries, such as aerospace, new energy, national defense and military, and other fields have put forward higher performance requirements. Therefore, the preparation of a high-performance alloy material with multiple advantages has become a research hotspot. Against this background, high entropy alloys (High Entropy Alloys) have been proposed. Due to their breakthrough design concept and unique physical, chemical and mechanical properties, high entropy alloy materials have attracted extensive research and attention worldwide. High entropy alloys combine the excellent properties of multiple elements, such as good mechanical properties, corrosion resistance and possible magnetic properties. High entropy alloys are usually alloys containing multiple (5 to 13) main elements, with a simple crystal phase structure, tend to form a single solid solution crystal phase, and can produce unusual mechanical properties. "Chemical disorder" is introduced by mixing multiple main elements. Unlike traditional alloys, high entropy alloys have no dominant elements or principal elements. They are a new type of alloy material with unique structural and performance characteristics.

[0003] High entropy alloys exhibit excellent mechanical properties, corrosion resistance and high temperature performance. Due to their excellent comprehensive performance, high entropy alloys are applied to extreme environments such as high temperature, high pressure, and corrosive liquids to increase the service life of workpieces. In recent years, the research on high entropy alloy films has made many breakthroughs, including the preparation of new high entropy alloy films, the improvement of synthesis methods, and the optimization of performance. However, the crystal phase structure and composition of existing high entropy alloy films are difficult to control, and expensive instruments and equipment are required, resulting in high production costs. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high entropy alloy film with adjustable components and crystal phase, so as to solve the problems that the crystal phase structure and composition of the existing high entropy alloy film are difficult to control, and expensive instruments and equipment are required, resulting in high production costs.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a high entropy alloy film with adjustable composition and crystal phase, which is specifically implemented according to the following steps:

[0006] Step 1, cutting the Si wafer into square pieces;

[0007] Step 2, turn on the magnetron sputtering system, install the FeCoNi ternary equiatomic ratio alloy target at target position 1, install the Mo metal target at target position 2, and install the Cu metal target at target position 3, then turn on the cooling water system, then place the square piece in the center of the sample tray and put it into the vacuum chamber cavity, and finally evacuate the vacuum chamber;

[0008] Step 3, turn on the vacuum indicator, control the rotation speed of the sample stage to 5 r / min, introduce pure Ar gas as sputtering gas, and control the flow rate of Ar gas to maintain the vacuum degree;

[0009] Step 4, set the sputtering power and sputtering time, open the target baffle, start sputtering, and obtain a high entropy alloy film.

[0010] As a preferred technical solution of the present invention, in step 1, a Si wafer with a diameter of 100 mm is cut into square pieces of 10 mm×10 mm.

[0011] As a preferred technical solution of the present invention, in step 1, the square piece is cleaned with deionized water, cleaned with acetone, and cleaned with anhydrous ethanol using ultrasonic waves.

[0012] As a preferred technical solution of the present invention, in step 1, the cooling water temperature in the cooling water system is set to 17.5°C-18.5°C.

[0013] As a preferred technical solution of the present invention, in step 2, the vacuum is evacuated to 2×10 -2 Pa-5×10 - 2 Pa.

[0014] As a preferred technical solution of the present invention, in step 2, the vacuum degree is maintained at 5×10 -2 Pa.

[0015] As a preferred technical solution of the present invention, in step 2, a Mo metal target is installed at target position 2, and a Cr metal target is installed at target position 3.

[0016] As a preferred technical solution of the present invention, in step 2, a Cr metal target is installed at target position 2, and a Cu metal target is installed at target position 3.

[0017] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a high-entropy alloy film with adjustable components and crystal phases, during the preparation process the crystal phase structure and composition of the high-entropy alloy film can be controlled, the preparation method is simple, and the production cost is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 The surface morphology of the FeCoNiCuMo high entropy alloy film prepared in Example 1 and the EDS element distribution diagram of each component;

[0020] Figure 2 1 is an X-ray diffraction XRD diagram of the FeCoNiCuMo high entropy alloy film prepared in Example 1 at different Mo target sputtering powers (40-70W);

[0021] Figure 3 The microhardness and elastic modulus of the FeCoNiCuMo high entropy alloy film prepared in Example 1 at different Mo target sputtering powers (40-70W);

[0022] Figure 4 The surface morphology of the FeCoNiCrMo high entropy alloy film prepared in Example 2 and the EDS distribution diagram of each component element;

[0023] Figure 5 1 is the XRD pattern of the FeCoNiCrMo high entropy alloy film prepared in Example 2 at different Mo target sputtering powers (30-50W);

[0024] Figure 6 The microhardness and elastic modulus of the FeCoNiCrMo high entropy alloy film prepared in Example 2 at different Mo target sputtering powers (30-50W);

[0025] Figure 7 The surface morphology of the FeCoNiCuCr high entropy alloy film prepared in Example 3 and the EDS distribution diagram of each component element;

[0026] Figure 8 is the X-ray diffraction XRD pattern of the FeCoNiCuCr high entropy alloy film prepared in Example 3 under different Cr target sputtering powers (40-70W);

[0027] Fig. 9 The microhardness and elastic modulus of the FeCoNiCuCr high entropy alloy film prepared in Example 3 under different Cr target sputtering powers (40-70W). DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0029] The method for preparing a high-entropy alloy film with adjustable components and crystal phase of the present invention is specifically implemented according to the following steps:

[0030] Step 1, cutting a Si wafer with a diameter of 100 mm into square pieces of 10 mm×10 mm, and performing deionized water cleaning, acetone cleaning, and anhydrous ethanol ultrasonic cleaning on the square pieces to remove the debris and large particles of dust left on the square pieces due to cutting, as well as the moisture on the surface of the object, the residual acetone, and other possible water-soluble dirt;

[0031] Step 2: Turn on the magnetron sputtering system, install FeCoNi ternary equiatomic alloy target at target position 1, Mo metal target at target position 2, and Cu metal target at target position 3. Then turn on the cooling water system and set the cooling water temperature to 17.5°C-18.5°C. Then, place the square piece in the center of the sample tray and put it into the vacuum chamber. Finally, evacuate to 2×10 - 2 Pa-5×10 -2 Pa;

[0032] Step 3: Turn on the vacuum indicator, control the rotation speed of the sample stage to 5 r / min, introduce pure Ar gas as the sputtering gas, and control the flow rate of Ar gas to keep the vacuum degree at 5×10 -2 Pa;

[0033] Step 4, set the sputtering power and sputtering time, open the target baffle, start sputtering, and obtain a high entropy alloy film.

[0034] Example 1

[0035] The present invention provides a method for preparing a high entropy alloy film with adjustable components and crystal phase, which is specifically implemented according to the following steps:

[0036] Step 1, cutting a Si wafer with a diameter of 100 mm into square pieces of 10 mm×10 mm, and performing a deionized water cleaning treatment, an acetone cleaning treatment, and an ultrasonic cleaning treatment of anhydrous ethanol on the square pieces for 10 minutes to remove the debris and large particles of dust left on the square pieces due to cutting, as well as the moisture on the surface of the object, the residual acetone, and other possible water-soluble dirt;

[0037] Step 2: Turn on the magnetron sputtering system, install FeCoNi ternary equiatomic alloy target at target position 1, Mo metal target at target position 2, and Cu metal target at target position 3. Then turn on the cooling water system and set the cooling water temperature to 17.5°C. Then, place the square piece in the center of the sample tray and put it into the vacuum chamber. Finally, evacuate to 2×10 -2 Pa;

[0038] Step 3: Turn on the vacuum indicator, control the rotation speed of the sample stage to 5 r / min, introduce pure Ar gas as the sputtering gas, and control the flow rate of Ar gas to keep the vacuum degree at 5×10 -2 Pa;

[0039] Step 4, set the sputtering power of target No. 2 to 70 W, the sputtering power of target No. 3 to 30 W, the sputtering time to 1800 s, open the target baffle, start sputtering, and obtain a high entropy alloy film.

[0040] The surface morphology of the film and the elemental composition of the high entropy alloy were analyzed using a scanning electron microscope. The SEM surface morphology and EDS element distribution of the FeCoNiCuMo high entropy alloy film were shown in Figure 2. Figure 1 As shown, Figure 1 When the Mo target sputtering power is 70 W, the surface morphology, EDS and element distribution diagram of the FeCoNiCuMo series high entropy alloy film: (a) area is the surface morphology, (b) area is the EDS layer diagram, (c) area is Fe, (d) area is Co, (e) area is Ni, (f) area is Cu, and (g) area is Mo. The elements are randomly and evenly distributed, and as shown in Table 1, the prepared film meets the definition of high entropy alloy.

[0041] Table 1 Element composition atomic percentage content (at%) of FeCoNiCuMo high entropy alloy film

[0042]

[0043] Figure 2 The X-ray diffraction XRD patterns of FeCoNiCuMo high entropy alloy films prepared under different Mo target sputtering powers (40-70W). It can be seen from the XRD pattern that, except for the diffraction peak on the Si substrate, there is only one alloy diffraction peak, indicating that the FeCoNiCuMo high entropy alloy film prepared this time is not a complex polycrystalline structure, but a single crystal FCC structure (diffraction peak corresponding to 44°), and the FCC crystal phase diffraction peak tends to be oriented to the (111) crystal plane. When the power of the Mo target increases, the peak half-width (FWHM) of the FCC (111) crystal plane decreases, and the diffraction peak intensity increases, indicating that when the Mo content increases, the crystallization quality of the film on the (111) crystal plane is still good. According to the Scherrer formula, when the Mo target sputtering power is 40, 60W, and 70W, the grain size is 8.9nm, 9.2nm, and 10.8nm, respectively. The reason is that when the Mo target power increases in the range of 40W to 70W, the speed and energy of the particles reaching the substrate surface are still in an ideal state, which promotes the growth and crystallization of the film on the FCC (111) crystal plane. Therefore, the FeCoNiCuMo high entropy alloy film is a single-phase FCC structure.

[0044] Figure 3 The microhardness and elastic modulus of FeCoNiCuMo high entropy alloy films prepared under different Mo target sputtering powers (40-70W). Figure 3 From the data, it can be seen that with the increase of Mo target power, the microhardness of the film increases, but the value of the elastic modulus decreases and then increases. When the Mo target power is 70W, the microhardness and elastic modulus of the prepared film both reach the maximum value, which are 7.98GPa and 203.47GPa respectively. This shows that the addition of a certain amount of Mo element is beneficial to improving the hardness and elastic modulus of the film. The atomic radius of Mo is the largest among the alloy components. Its addition can produce a lattice distortion effect in the alloy solid solution, hinder dislocation movement, and increase the hardness of the alloy.

[0045] Example 2

[0046] The present invention provides a method for preparing a high entropy alloy film with adjustable components and crystal phase, which is specifically implemented according to the following steps:

[0047] Step 1, cutting a Si wafer with a diameter of 100 mm into square pieces of 10 mm×10 mm, and performing deionized water cleaning, acetone cleaning, and anhydrous ethanol ultrasonic cleaning on the square pieces to remove the debris and large particles of dust left on the square pieces due to cutting, as well as the moisture on the surface of the object, the residual acetone, and other possible water-soluble dirt;

[0048] Step 2: Turn on the magnetron sputtering system, install FeCoNi ternary equiatomic alloy target at target position 1, Mo metal target at target position 2, and Cr metal target at target position 3, then turn on the cooling water system and set the cooling water temperature to 18 °C. Then, place the square piece in the center of the sample tray and put it into the vacuum chamber, and finally evacuate to 3×10 -2 Pa;

[0049] Step 3: Turn on the vacuum indicator, control the rotation speed of the sample stage to 5 r / min, introduce pure Ar gas as the sputtering gas, and control the flow rate of Ar gas to keep the vacuum degree at 5×10 -2 Pa;

[0050] Step 4, set the sputtering power of target No. 2 to 50 W, the sputtering power of target No. 3 to 60 W, the sputtering time to 1800 s, open the target baffle, start sputtering, and obtain a high entropy alloy film.

[0051] The SEM surface morphology of FeCoNiCrMo high entropy alloy film is shown in Figure 4As shown in Table 2, the elements are randomly and evenly distributed, and as shown in Table 2, the prepared film meets the definition of high entropy alloy. When the Mo target power is 50W, the surface of the high entropy alloy film is covered with fine and evenly distributed particles, no significant particle aggregates or agglomerates are observed, and the surface is very smooth with very few defects, which meets the typical characteristics of amorphous films.

[0052] Table 2 Element composition atomic percentage content (at%) of FeCoNiCrMo high entropy alloy film

[0053]

[0054] Figure 4 When the Mo target sputtering power is 50 W, the surface morphology, EDS and element distribution diagram of the FeCoNiCrMo high-entropy alloy film: (a) area is the surface morphology, (b) area is the EDS layered diagram, (c) area is Fe, (d) area is Co, (e) area is Ni, (f) area is Cr, and (g) area is Mo.

[0055] Figure 5 The X-ray diffraction XRD patterns of FeCoNiCrMo high entropy alloy films prepared under different Mo target sputtering powers (30-50W). It can be seen from the XRD pattern that FeCoNiCrMo high entropy alloys have three main diffraction peaks, which correspond to Cr-rich BCC, FCC, and FCC structures (diffraction peaks corresponding to 40°, 43°, and 75°). Among them, the BCC crystal phase structure tends to be (110) oriented. The diffraction peak at 50W becomes flat, indicating that the film has poor crystallinity and is amorphous under this sputtering power.

[0056] The formation of amorphous structure of high entropy alloy is the result of the combined effects of high entropy effect, hysteresis diffusion effect and lattice distortion effect. The specific reasons are as follows: (1) The structural characteristics of high entropy alloys show that as the number of elements in the system increases, the mixing entropy of the system also increases, resulting in a significant decrease in the Gibbs free energy of the system. During the solidification process, the system is more inclined to form a simple solid solution, and is often accompanied by the generation of nanostructures or amorphous phases. (2) In a multi-component system, the difference in atomic size will destroy the periodicity of atomic arrangement, resulting in a large lattice distortion in the system. Lattice distortion can reduce the crystallization ability of the crystal, hinder lattice growth, and thus promote the formation of amorphous structure. (3) Fast atomic stacking rate and slow diffusion are ideal conditions for the formation of amorphous structure. Due to the large number of elements in high entropy alloys and the large difference in atomic size, the stacking density of the system is high, and the diffusion between atoms becomes complex and difficult. In addition, magnetron sputtering technology has a very fast cooling rate (>104K / s) and atomic deposition rate, so that when the atoms just reach the Si substrate, the atomic nucleation time in the alloy is insufficient and the movement and diffusion rate is low. Therefore, more energy is required to complete the crystal phase change process, and the crystal phase change process is slow, which inhibits the nucleation and growth process of the crystalline phase, meeting the conditions for the formation of an amorphous structure.

[0057] Figure 5 X-ray diffraction (XRD) patterns of FeCoNiCrMo high entropy alloy films prepared at different Mo target sputtering powers (30-50W).

[0058] Figure 6 The microhardness and elastic modulus of FeCoNiCrMo high entropy alloy films prepared under different Mo target sputtering powers (30-50W). Figure 6 From the data, it can be seen that with the increase of Mo target power, the microhardness of the film increases, but the value of the elastic modulus first increases and then decreases. When the Mo target power is 50W, the microhardness of the prepared film reaches the maximum value, and when the Mo target power is 40W, the elastic modulus of the prepared film reaches the maximum value, which are 10.094GPa and 203.467GPa respectively. In the FeCoNiCrMo high entropy alloy film, the phenomenon that the elastic modulus first increases and then decreases with the Mo content is because the addition of Mo may cause an ordered BCC structure to appear in the alloy, and this ordering usually increases the elastic modulus. Excessive Mo causes the alloy to transform from an ordered structure to a disordered structure (amorphous structure), and this transformation may reduce the elastic modulus.

[0059] Figure 6 Microhardness and elastic modulus of FeCoNiCrMo high entropy alloy films prepared at different Mo target sputtering powers (30-50W). (Unit: GPa)

[0060] Example 3

[0061] The present invention provides a method for preparing a high entropy alloy film with adjustable components and crystal phase, which is specifically implemented according to the following steps:

[0062] Step 1, cutting a Si wafer with a diameter of 100 mm into square pieces of 10 mm×10 mm, and performing deionized water cleaning, acetone cleaning, and anhydrous ethanol ultrasonic cleaning on the square pieces to remove the debris and large particles of dust left on the square pieces due to cutting, as well as the moisture on the surface of the object, the residual acetone, and other possible water-soluble dirt;

[0063] Step 2: Turn on the magnetron sputtering system, install FeCoNi ternary equiatomic alloy target at target position 1, install Cr metal target at target position 2, and install Cu metal target at target position 3. Then turn on the cooling water system and set the cooling water temperature to 18.5°C. Then, place the square piece in the center of the sample tray and put it into the vacuum chamber. Finally, evacuate to 5×10 -2 Pa;

[0064] Step 3: Turn on the vacuum indicator, control the rotation speed of the sample stage to 5 r / min, introduce pure Ar gas as the sputtering gas, and control the flow rate of Ar gas to keep the vacuum degree at 5×10 -2 Pa;

[0065] Step 4, set the sputtering power of target No. 2 to 70 W, the sputtering power of target No. 3 to 30 W, the sputtering time to 1800 s, open the target baffle, start sputtering, and obtain a high entropy alloy film.

[0066] SEM surface morphology of FeCoNiCuCr high entropy alloy film Figure 7 As shown. Each element is randomly and evenly distributed, and as shown in Table 3, the prepared film meets the definition of high entropy alloy. From the surface morphology picture, the surface of the film is composed of nano-spherical particles of different shapes and sizes, each particle has a fine island structure inside, and the particle size on the surface of the film is small and unevenly distributed. This is attributed to the fact that when the sputtering power of the Cr target is low, the energy of the particles sputtered from the target is low, the deposition rate is slow, the probability of reaching the substrate is small, and the diffusion capacity between particles is limited. However, the deposition of high-energy particles also increases the temperature of the substrate and promotes the crystallization process of the film, resulting in poor film-forming ability during the film formation process, uneven surface, but continuous grains. When the sputtering power increases, the particle size decreases to a certain extent, the film has good bonding with the substrate, and no cracking or peeling is observed.

[0067] Table 3 Element atomic content (at%) of FeCoNiCuCr high entropy alloy films

[0068]

[0069] Figure 7 When the Cr target sputtering power is 70 W, the surface morphology, EDS and element distribution diagram of the FeCoNiCuMo high-entropy alloy film: (a) area is the surface morphology, (b) area is the EDS layered diagram, (c) area is Fe, (d) area is Co, (e) area is Ni, (f) area is Cu, and (g) area is Cr.

[0070] like Figure 8 The XRD patterns of FeCoNiCuCr high entropy alloy films prepared under different Cr target sputtering powers (40-70W) are shown. It can be seen from the XRD pattern that FeCoNiCuCr high entropy alloy has four main diffraction peaks, which are Cr-rich BCC, FCC, FCC, and FCC structures (diffraction peaks corresponding to 41°, 44°, 50°, and 75°). It is observed that when the diffraction angles 2θ are 44°, 50°, and 75°, the corresponding sin2θ ratios are 3:4:8, which also indicates that the crystal structure is FCC (face-centered cubic). Under different Cr target sputtering powers, the diffraction peak intensity of the (111) crystal plane is stronger than that of other crystal planes, which indicates that the growth of the crystal on the (111) crystal plane is more significant. Therefore, the FeCoNiCuCr high entropy alloy film is a FCC+BCC dual-phase structure. When the Cr target sputtering power is 40W, 60W, and 70W, the grain sizes are 14.2nm, 13.5nm, and 13.8nm.

[0071] Fig. 9 Microhardness and elastic modulus of FeCoNiCuCr high entropy alloy films prepared under different Cr target sputtering powers (40-70W). With the increase of Cr target power, the microhardness of the film first decreases and then increases, and the value of the elastic modulus is decreasing. When the Cr target sputtering power increases from 60W to 70W, the elastic modulus decreases significantly. With the increase of Cr content, a Cr-rich BCC crystal phase structure is formed in the alloy, resulting in crystal phase precipitation, and the microhardness and elastic modulus of the alloy decrease, but the BCC crystal phase structure is conducive to increasing the hardness of the film, so when the Cr content increases, the hardness also increases. Cr affects the grain size of the alloy, and grain refinement helps to improve the microhardness and elastic modulus, but excessive addition of Cr leads to grain growth, which reduces the microhardness and elastic modulus. Therefore, the increase in Cr content should be appropriate to improve the mechanical properties of FeCoNiCrCu high entropy alloys.

[0072] The above description shows and describes several preferred embodiments of the invention, but as mentioned above, it should be understood that the invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall be within the scope of protection of the claims attached to the invention without departing from the spirit and scope of the invention.

Claims

1. A method for preparing a high-entropy alloy film with adjustable composition and crystal phase, characterized in that: Follow the steps below to implement it: Step 1, cutting the Si wafer into square pieces; Step 2, turn on the magnetron sputtering system, install the FeCoNi ternary equiatomic ratio alloy target at target position 1, install the Mo metal target at target position 2, and install the Cu metal target at target position 3, then turn on the cooling water system, then place the square piece in the center of the sample tray and put it into the vacuum chamber cavity, and finally evacuate the vacuum chamber; Step 3, turn on the vacuum indicator, control the rotation speed of the sample stage to 5 r / min, introduce pure Ar gas as sputtering gas, and control the flow rate of Ar gas to maintain the vacuum degree; Step 4, set the sputtering power and sputtering time, open the target baffle, start sputtering, and obtain a high entropy alloy film.

2. The method for preparing a high-entropy alloy thin film with adjustable composition and crystal phase according to claim 1, characterized in that: In the step 1, a Si wafer with a diameter of 100 mm is cut into square pieces with a size of 10 mm×10 mm.

3. The method for preparing a high-entropy alloy thin film with adjustable composition and crystal phase according to claim 1, characterized in that: In the step 1, the square piece is cleaned with deionized water, cleaned with acetone, and cleaned with anhydrous ethanol using ultrasonic waves.

4. The method for preparing a high-entropy alloy thin film with adjustable composition and crystal phase according to claim 1, characterized in that: In step 1, the cooling water temperature in the cooling water system is set to 17.5°C-18.5°C.

5. The method for preparing a high-entropy alloy thin film with adjustable composition and crystal phase according to claim 1, characterized in that: In step 2, the vacuum is evacuated to 2×10 -2 Pa -5×10 -2 Pa.

6. The method for preparing a high-entropy alloy thin film with adjustable composition and crystal phase according to claim 1, characterized in that: In step 2, the vacuum degree is maintained at 5×10 -2 Pa.

7. The method for preparing a high-entropy alloy thin film with adjustable composition and crystal phase according to claim 1, characterized in that: In step 2, a Mo metal target is installed at target position 2, and a Cr metal target is installed at target position 3.

8. The method for preparing a high-entropy alloy thin film with adjustable composition and crystal phase according to claim 1, characterized in that: In step 2, a Cr metal target is installed at target position 2, and a Cu metal target is installed at target position 3.

Citation Information

Patent Citations

  • Multi-element high-entropy alloy film and preparation method thereof

    CN103898463A

  • Physical vapor deposition preparation method for high-entropy alloy film with uniform and controllable components

    CN111074223A

  • Preparation method of high-entropy alloy thin film

    CN111926303A

  • FeCoNiCrTiV high-entropy alloy film and preparation method thereof

    CN113355580A

  • Mo-Ta-W refractory high-entropy alloy film and preparation method thereof

    CN114015996A